(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines the linguaculturological aspects of Uzbek dramas and analyzes the relationship between language and culture in dramatic discourse. Uzbek dramas reflect national identity traditions, customs, moral values, and communicative behavior through culturally marked vocabulary, proverbs, phraseological units, speech etiquette, and symbolic expressions. The study focuses on the works of Uzbek playwrights such as Abdulla Qahhor, Hamza Hakimzoda Niyoziy, and Sharof Boshbekov. Examples from dramas including Temir Xotin and Boy ila Xizmatchi demonstrate how dramatic language preserves Uzbek cultural heritage and national mentality. The article concludes that Uzbek dramas serve as important cultural and linguistic sources for understanding the worldview, traditions, and spiritual values of the Uzbek people.